Strategic role of supply chain management in logistics: A case study at Yusen Logistics Malaysia - Arvin a/l Ravichandran (2024)
This case study discusses the critical role of supply chain management in the operations of Yusen Logistics Malaysia, one of the industry's leading logistics organisations. It looks at how the company's supply chain strategy comply with its overall goals and contribute to its competitive advantage. Yusen Logistics Malaysia has established business as a leading logistics supplier in the area by focusing on efficiency, innovation, and customer-centricity. This study provides insights into how supply chain management improves operational performance, optimises resource utilisation, and fosters collaboration across the logistics network. Yusen Logistics Malaysia has made major improvements to its logistics processes by employing advanced technology and implementing best practices. These enhancements have resulted in reduced lead times and improved overall service quality. The case study